New aspects of the genetic disposition of various forms of chronic nephritic syndrome in children. (Journal of Universal Science Research, 2023)
Knowing hereditary predisposition, in the system of general medical examination of the child population, it is recommended to single out a group of children with chronic nephritic syndrome due to a genetic predisposition as a high-risk group and conduct dispensary observation.The revealed associations of the relationship between the GG genotype of the MMP9 (A-8202G) rs11697325 gene and the development of the disease, in particular its nephrotic and mixed forms, serve as an important diagnostic and prognostic marker of this pathology and the approach to timely treatment.